ANALISIS ANGGARAN PROYEK SEBAGAI ALAT PENGENDALIAN BIAYA PADA NEVERLAND DEVELOPMENT (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
The purpose of this research is to explain the function of budget planning of project cost as a tool of cost control at company and form of control which will bedone by company management in reducing existence of deviation. The data was obtained directly from Purworejo's Neverland Development company. This research uses variance analysis method, data obtained in the form of budget plan and its realization as well as direct interview. Based on the result of the research, the difference between budget of project cost and its realization happened the advantageous difference in the calculation of three types of cost, namely direct material, direct labor and the difference of project overhead cost. This means that, the cost budget can be used as a cost control tool within the company. Cost budgeting can be made as a work guide or reference in the creation of a company project in evaluating the cost control that occurs in the company. With the budget will reduce unexpected expenses and other costs beyond the budget